2005
DOI: 10.1086/431513
|View full text |Cite
|
Sign up to set email alerts
|

Projected Cost‐Effectiveness of Rotavirus Vaccination for Children in Asia

Abstract: A rotavirus vaccine could be cost-effective, depending on the income level of the country, the price of the vaccine, and the cost-effectiveness standard that is used. Decisions regarding implementation of vaccine use should be based not only on whether the intervention provides a cost savings but, also, on the value of preventing rotavirus disease-associated morbidity and mortality, particularly in countries with a low income level (according to 2004 World Bank criteria for the classification of countries into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 35 publications
8
71
1
6
Order By: Relevance
“…Our estimate of 7.8 per 1,000 children a year aged less than fi ve requiring hospitalisation for RV-AGE corresponds to a cumulative incidence of 38.7 per 1,000 children requiring hospitalisation by age fi ve. This is considerably higher than a recent US estimate (12.5 per 1,000), 10 but is comparable with a recent average estimate for Korea, Japan and Hong Kong (41.5 per 1,000) 11 and for China, Malaysia and Thailand (45.9 per 1,000), 11 and is considerably lower than a recent estimate for Argentina (83 per 1,000). 12 The reason for the low hospitalisation rate estimate for the US may be due in part to an overly conservative methodology (the residual method, which assumes that no hospital cases in the off-season are attributable to rotavirus).…”
Section: General Practitioner (Gp) Visitssupporting
confidence: 53%
“…Our estimate of 7.8 per 1,000 children a year aged less than fi ve requiring hospitalisation for RV-AGE corresponds to a cumulative incidence of 38.7 per 1,000 children requiring hospitalisation by age fi ve. This is considerably higher than a recent US estimate (12.5 per 1,000), 10 but is comparable with a recent average estimate for Korea, Japan and Hong Kong (41.5 per 1,000) 11 and for China, Malaysia and Thailand (45.9 per 1,000), 11 and is considerably lower than a recent estimate for Argentina (83 per 1,000). 12 The reason for the low hospitalisation rate estimate for the US may be due in part to an overly conservative methodology (the residual method, which assumes that no hospital cases in the off-season are attributable to rotavirus).…”
Section: General Practitioner (Gp) Visitssupporting
confidence: 53%
“…It is obvious that the direct costs of diarrhea vary according to country's level of development and the type of health system it applies. For example, in Asia the medical costs of diarrhea are different for low income ($29 million), middle ($114 million) and high income countries ($46 million) [15].…”
Section: Discussionmentioning
confidence: 99%
“…As suggested in the literature, rotavirus is a very common cause of severe diarrhea and hospitalization for children under age of five in developed [12,14,16] and developing countries [4]. Numerous studies have shown that rotavirus immunization programs might be cost-effective, even though many aspects have to be taken into consideration such as morbidity and mortality rates due to rotavirus and vaccine price [7,12,13,15]. Besides the actual costs of diarrhea, these very important aspects related to rotavirus immunization should be investigated through carefully designed future studies, in order to help the decision makers to opt for a vaccination program or other potential interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Confusion between I$ from Goldie et al, 2007(Goldie et al, 2007 and US$ (I$ higher than US$ 7.3 Rotavirus Since the rotavirus vaccine can be administered at the same time as the current recommended tetravalent DTPw-Hib and OPV vaccines, incremental administration costs were assumed to be low. Both administration costs (US$1, in BRL2004, exchange rate: US$1 = BRL2.65, Brazilian Central Bank) and expected losses from waste (10% of vaccine doses) were taken from the literature, as no local data were available (Podewils et al, 2005;192 (suppl 1):S133-45.) (Podewils et al, 2005) De Soárez et al 2008 (de Soarez et al, 2008) 4.96 …”
Section: 3mentioning
confidence: 99%
“…Both administration costs (US$1, in BRL2004, exchange rate: US$1 = BRL2.65, Brazilian Central Bank) and expected losses from waste (10% of vaccine doses) were taken from the literature, as no local data were available (Podewils et al, 2005;192 (suppl 1):S133-45.) (Podewils et al, 2005) De Soárez et al 2008 (de Soarez et al, 2008) 4.96 …”
Section: 3mentioning
confidence: 99%